P46 Ethnic differences in pace of growth between birth and 5 years: results from the millennium cohort study. (16th November 2010) - Lenguerrand, E; Harding, S
Abstract : Objective: Size at birth and accelerated postnatal growth are linked to obesity and cardiovascular disease (CVD) in adulthood. CVD is more common in Black African and South Asian origin populations in the UK. Little is known about growth trajectories of ethnic minority children in the UK. Overweight is more common in some ethnic minority groups in adolescence. We examined ethnic differences in growth between birth and 5 years (y). Design: Millennium Cohort Study, a UK population-based cohort study. Setting: England. Participants: White (6361), Black Caribbean (152), Black African (250), Indian (328), Pakistani (645) and Bangladeshi (265) infants born in 2000–2001, ≥2500 g, ≥36 weeks gestation, with no physical disability. Main Outcome Measures: Weight, height, body mass index (BMI) and age-standardised Z-scores (based on the British 1990 growth reference). Weight was measured at birth, 9 months, 3 y and 5 y and linear mixed models were used to estimate differences in the weight trajectories and to identify potential differential effects from maternal characteristics (age and smoking status at delivery, education, psychological well-being, diabetic status), household socio-economic circumstances (SEC) (employment, poverty level), and feeding practices (duration of breastfeeding, age at first solid food). Results: Compared with White infants, mean birth weights of Indian, Pakistani Bangladeshi and Black Caribbean infants were lower by 180–410 g while that of Black African infants were similar. Relative to the standard, all ethnic groups experienced faster weight gain notably between 0–3 y. Average weight gains between 0–5 y were greater for Black Caribbeans (boys +0.88 sd/year, girls +0.37 sd/year) and Black Africans (+0.78/year, +0.30/year) than for Whites (+0.45/year, +0.17/year). The increase was non-linear with slowest weight gain as age increased especially for Black Caribbeans and Africans boys (−0.18 sd/y 2, 95% CI −0.23 to −0.14). By age 5 y, these groups were the heaviest but also the tallest. Larger BMIs were observed for Black Caribbean boys (1.32, 0.71 to 1.94) and Black African girls (0.97, 0.72 to 1.22) than their White peers. At this age, Black Caribbean boys (56.2 cm, 53.9 to 58.6) and Black African girls (55.8 cm, 54.7 to 56.8) also had larger waist circumference than Whites (boys 53.7 cm, girls 53.5 cm). There were no ethnic specific effects from maternal factors, household SEC or feedings practices. Conclusions: A pattern of lighter birth weights and rapid growth was observed for Black Africans origin children compared with White children. The growth patterns observed here may be pertinent to the development of ethnic differences in CVD.